Reserve Accumulation, Macroeconomic Stabilization, and Sovereign Risk - Bianchi, Javier; Sosa-Padilla, César (Review of Economic Studies, 2024)
Abstract In the past three decades, governments in emerging markets have accumulated large amounts of international reserves, especially those with fixed exchange rates. This article proposes a theory of reserve accumulation that can account for these facts. Using a model of endogenous sovereign default with nominal rigidities, we argue that the interaction between sovereign risk and aggregate demand amplification generates a macroeconomic-stabilization hedging role for international reserves. We show that issuing debt to purchase reserves during good times allows the government to stabilize aggregate demand when sovereign spreads rise and rolling over the debt becomes more expensive. We provide empirical evidence consistent with the model’s predictions.